Multi-objective sensitivity analysis of shell-and-tube LHTES performance - Fornarelli Francesco (EDP Sciences, 2021)
In the present paper a sensitivity analysis has been carried out concerning the charging/discharging time and the stored energy performances of a shell-and-tube LHTES with respect to the number of tubes and the tube internal radius. The aim of this analysis is to investigate how the design variables affect the LHTES performance. this could lead to determine the thermal storage optimal design. Thus, the sensitivity analysis has a key role in the selection of several acceptable solutions. The considered LHTES exhibits a cylindrical shell geometry characterized by constant height and diameter. This aspect has allowed to employ simplified theoretical models able to predict the charging/discharging time and the stored energy performance. These models consider a constant heat exchange wall temperature whereas the heat exchange area and the whole PCM volume vary according to the design variables. This analysis represents the first step to solve the multi-objective optimization of the thermal storage design problem and then to determine the best solutions in both design variables and thermal storage performance domains.